2015
DOI: 10.1109/tpel.2014.2366431
|View full text |Cite
|
Sign up to set email alerts
|

Investigating a <sc>MOSFET</sc> Driver (Buffer) Circuit Transition Ringings Using an Analytical Model

Abstract: In this paper, a new analytical model introduced extracting from datasheet of a MOSFET and developed a MATLAB code for simulating a MOSFET driver circuit is proposed in the literature to observe the ringings of its output for capacitively loaded case. The output waveform is studied only for high-to-low transition. Gate drive resistance, wiring parasitics of the printed circuit board layout, and the characteristic properties of the MOSFET affect both the delay time of the MOSFET to become ON and performance of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…In a complicated resonance process, the impact of individual inductances (L d , L g , L s ) on the oscillation is different. Analytical (Xiao et al, 2004;Ren et al, 2006;Zhang et al, 2008;Li et al, 2011;Wang et al, 2012;Alexakis et al, 2013;Raee et al, 2013;Takao and Ohashi, 2013;Azizouglu and Karaca, 2014;Nayak and Hatua, 2016;Xie et al, 2016) and empirical methods (Chen, 2009;Chen et al, 2010;Zhang et al, 2012;Chen et al, 2013a;Stewart et al, 2013;Wada et al, 2013;Anthon et al, 2014;Noppakunkajorn et al, 2014;Noppakunkajorn et al, 2015;Walder and Yuan, 2015;Wang X. et al, 2017) have been reported that investigated the impact of different parasitic inductance on oscillation. As shown in Figure 3B, it is concluded that the impact of L g on damped oscillation is negligible and the main contributor is L d (Chen, 2009;Khanna et al, 2013).…”
Section: Damped Oscillations In V Dsmentioning
confidence: 99%
“…In a complicated resonance process, the impact of individual inductances (L d , L g , L s ) on the oscillation is different. Analytical (Xiao et al, 2004;Ren et al, 2006;Zhang et al, 2008;Li et al, 2011;Wang et al, 2012;Alexakis et al, 2013;Raee et al, 2013;Takao and Ohashi, 2013;Azizouglu and Karaca, 2014;Nayak and Hatua, 2016;Xie et al, 2016) and empirical methods (Chen, 2009;Chen et al, 2010;Zhang et al, 2012;Chen et al, 2013a;Stewart et al, 2013;Wada et al, 2013;Anthon et al, 2014;Noppakunkajorn et al, 2014;Noppakunkajorn et al, 2015;Walder and Yuan, 2015;Wang X. et al, 2017) have been reported that investigated the impact of different parasitic inductance on oscillation. As shown in Figure 3B, it is concluded that the impact of L g on damped oscillation is negligible and the main contributor is L d (Chen, 2009;Khanna et al, 2013).…”
Section: Damped Oscillations In V Dsmentioning
confidence: 99%
“…The WJ112‐1A type relays J 4 – J 8 are utilised to connect and disconnect inductors L 2– L 6 for adjusting the pulse edges’ commutating rate d I f /d t . After pulse passing through different inductors, the values of d I f /d t can be modulated due to electromagnetic induction involving in there [12, 13] . The relays J 4 – J 7 are controlled by the chip IC8 aforesaid, while J 8 is regulated by a SN75452 type peripheral driver IC16, as demonstrated in the main control circuit.…”
Section: Design Of Main Circuitsmentioning
confidence: 99%
“…The CFOA controls the gate of the MOSFET Q2 via resistor R5. This prevents parasitic oscillations and ringing of the MOSFET[34].…”
mentioning
confidence: 99%